Does Reward Gamification Drive Brand Relationship Quality?: An Experimental Approach. Issue 4 (19th May 2022) - Shankar, Amit
Abstract: This study examines the impact of reward gamification on brand relationship quality (BRQ) in the mobile banking (m-banking) context. The study also examines the mediating effect of brand engagement and how the effect varies at different levels of personal innovativeness. A scenario-based experimental design was used to examine the effect of reward gamification on BRQ. Data were collected from 259 m-banking users to examine the proposed hypotheses. The findings suggest that gamification has a significant impact on BRQ. This study contributes to the emerging gamification and m-banking literature and helps banks design gamified rewards programs to enhance BRQ.